Identification of undescribed Relb expression domains in the murine brain by new Relb:cre‐katushka reporter mice. Issue 8 (30th May 2020) - Engelmann, Christian; Riemann, Marc; Carlstedt, Swen; Grimlowski, Randy; Andreas, Nico; Koliesnik, Ievgen; Meier, Elke; Austerfield, Phillip; Haenold, Ronny
Abstract: Background: Noncanonical NF‐κB signaling through activation of the transcription factor RelB acts as key regulator of cell lineage determination and differentiation in various tissues including the immune system. To elucidate temporospatial aspects of Relb expression, we generated a BAC transgenic knock‐in mouse expressing the fluorescent protein Katushka and the enzyme Cre recombinase under control of the murine Relb promoter ( Relb Cre‐Kat mice). Results: Co‐expression of Katushka and Relb in fibroblast cultures and tissues of transgenic mice revealed highly specific reporter functions of the transgene. Crossing Relb Cre‐Kat mice with ROSA26R reporter mice that allow for Cre‐mediated consecutive β‐galactosidase or YFP synthesis identified various Relb expression domains in perinatal and mature mice. Besides thymus and spleen, highly specific expression patterns were found in different neuronal domains, as well as in other nonimmune organs including skin, skeletal structures and kidney. De novo Relb expression in the mature brain was confirmed in conditional knockout mice with neuro‐ectodermal Relb deletion. Conclusion: Our results demonstrate the usability of Relb Cre‐Kat reporter mice for the detection of de novo and temporarily restricted Relb expression including cell and lineage tracing of Relb expressing cells. Relb expression during mouse embryogenesis and at adulthood suggests, beyond immunity, important functions of this transcription factor in neurodevelopment and CNS function. Key Findings: Generation of a BAC transgenic knock‐in mouse expressing the fluorescent protein Katushka and the enzyme Cre recombinase under control of the murine Relb promoter ( Relb Cre‐Kat mice) to detect temporospatial Relb expression patterns. Co‐expression of Katushka and Relb in various cells and tissues of transgenic mice, including thymus and spleen, confirmed high specificity of the reporter construct. Crossing Relb Cre‐Kat mice with ROSA26R reporter mice that allow for Cre‐mediated consecutive CE B2‐galactosidase or YFP synthesis was used for cell and lineage tracing of RelbM expressing cells and identified various Relb expression domains in perinatal and mature mice. Expression patterns were also found in different neuronal domains, as well as in other non‐immune organs, demonstrating the usability of Relb Cre‐Kat reporter mice for the detection of de novo and temporarily restricted Relb expression. Relb expression during mouse embryogenesis and at adulthood suggests, beyond immunity, important functions of this transcription factor in neurodevelopment and CNS function.